حساب خصائص الديترون باستخدام تفاعلات غاوصية متوافقة مع النموذج الطبقي اللامتغير - دومة, صلاح; سلمان, حسن; سعيد, سامر (Latakia University Journal -Basic Sciences Series, 2019)
تم في هذا البحث حساب التابع الموجي للديترون في الحالة الأساسية ,اعتمادا على النموذج الطبقي اللامتغير باعتبار أن التأثير المتبادل بين النيكلونين يتألف من جهود مركزية و تنسورية وسبينية-مدارية من الدرجتين الأولى و الثانية . أما وسطاء (بارا مترات) هذا التأثير فقد اختيرت بحيث تلائم التجاذب عن بعد والتدافع عن قرب للنيكلونين , وتعطي توافقا" جيدا" مع المعطيات التجريبية لكل من طاقة ترابط الديترون ومتوسط مربع نصف قطره واحتمالية السوية D و العزم المغناطيسي وعزم رباعي الأقطاب الكهربائي. The basis of the translation invariant shell model is used to construct the ground–state wave function of deuteron. The interactions used consist of central, tensor, spin orbit and quadratic spin orbit terms. The parameters of these interactions are so chosen in such a way that they represent the long-range attraction and the short-range repulsion of the nucleon-nucleon interaction and to reproduce good agreement between the calculated values of the deuteron binding energy, root mean-square radius, D-state probability, magnetic dipole moment and electric quadrupole moment and the corresponding experimental values.